Collaboration and Co-creation New Platforms for Marketing and Innovation - Bhalla, Gaurav. (Springer New York : Imprint: Springer, 2011)
Praise for Collaboration and Co-Creation “In today’s customer-empowered world, collaboration and co-creation competencies are critical to the future growth of a company…Gaurav Bhalla offers a concrete framework and specific examples that managers can use to implement value co-creation programs with their customers. A must-read for companies not wishing to get left behind!” --Vijay Govindarajan, Earl C. Daum 1924 Professor of International Business, Tuck School of Business, Dartmouth College “Collaboration and co-creation is the sweet spot for rethinking how companies should practice marketing and innovation…Gaurav Bhalla’s book is very timely, and offers readers an effective way for building businesses around customers.” --Nicolas Mirzayantz, Group President, Fragrances, International Flavors and Fragrances “Companies can't afford to fake it. Customer-driven innovation has moved from the edge to become a core business practice. Gaurav Bhalla helps you understand what it takes to make this shift, and not a moment too soon.” --John Hagel III, Co-Chairman, Deloitte Center for the Edge, and co-author, The Power of Pull “If running your business seems more difficult lately, reading this book will help you understand why. It will also provide insights into how collaboration and co-creation can improve your company’s performance.” --Vince Barabba, Author, Meeting of the Minds, and Founder and Chairman, Market Insight Corporation “Gaurav Bhalla is after big game: how the world’s leading institutions are connecting and collaborating with their most important asset – their customers – in novel and important ways…This book is an important one to read for any marketing, market research, or product innovation professional.” --Steve Howe, CEO, Passenger “Based on my research it is clear that user co-creation is a strong driver for transforming the marketing and innovation programs of those companies that dare to listen and respond. Gaurav Bhalla provides a solid framework to guide this process and a rich set of case stories to explain why and how.” --Jacob Buur, Professor of Participatory Innovation, Research Director of SPIRE, University of Southern Denmark.